2017
DOI: 10.1080/10962247.2017.1330713
|View full text |Cite
|
Sign up to set email alerts
|

Near-roadway monitoring of vehicle emissions as a function of mode of operation for light-duty vehicles

Abstract: The paper provides emission factors (EFs) that are a function of traffic volume and mode of operation (free flow and congestion) for LDVs under real-world conditions. The good agreement between monitoring and modeling results indicates that high-resolution, simultaneous measurements of air quality and meteorological and traffic conditions can be used to determine real-world, fleet-wide vehicle EFs as a function of vehicle mode of operation under actual driving conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 15 publications
1
1
0
1
Order By: Relevance
“…It is noteworthy to mention that the GHG concentrations became remarkable over the common MSW transportation route of all provinces, starting after the junction crossing the routes 80 and 615 (404337 UTM Easting and 2910111 UTM Northing) and ending at the landfill site. The ground-level atmospheric distributions of GHG concentrations estimated in this study were in good agreement with those reported for urban districts using the similar methodology (Çetinkaya et al, 2018; Wen et al, 2017).…”
Section: Resultssupporting
confidence: 88%
“…It is noteworthy to mention that the GHG concentrations became remarkable over the common MSW transportation route of all provinces, starting after the junction crossing the routes 80 and 615 (404337 UTM Easting and 2910111 UTM Northing) and ending at the landfill site. The ground-level atmospheric distributions of GHG concentrations estimated in this study were in good agreement with those reported for urban districts using the similar methodology (Çetinkaya et al, 2018; Wen et al, 2017).…”
Section: Resultssupporting
confidence: 88%
“…Traffic volume also plays an important role in creating CO pollution (USEPA, 2014;Pan et al, 2016;Wen et al, 2017;Le et al, 2021;Wang et al, 2021). Increased traffic volume generally leads to higher emissions (Pan et al, 2016;USEPA, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Tendo em vista que os veículos são fontes importantes de poluição do ar, compreender a magnitude da poluição à qual os humanos estão expostos é importante para determinar o efeito das emissões veiculares na qualidade do ar próximo às avenidas e rodovias (WEN et al, 2017). Com base nas afirmações acima, este trabalho tem como objetivo analisar a dispersão do material particulado inalável de até 10 micrômetros de diâmetro (MP 10 ), proveniente de caminhões pesados em uma avenida da cidade de São Paulo -SP (Av.…”
Section: Introductionunclassified